Strength and conditioning off-season programming for high school swimmers - Waller, M.; Shim, A.; Piper, T. (Strength and Conditioning Journal, 2019)
Competition swimming has different categories of distances, individual, relay, and swim strokes that all require physical performance to succeed. An effective dry-land plan that uses both upper- and lower-body programming can improve swimmer strength, power, swim efficiency, and injury prevention. The current programming is specific to the off-season training for high school level swimmers that have general preparation and special preparation phases. These phases have tests for monitoring purposes, strength training, power exercises, and injury prevention outlined in the program.